Sudden Unexpected Death due to Chiari Type I Malformation in a Road Accident Case. Issue 2 (27th December 2012) - Zhang, Jianhua; Shao, Yu; Qin, Zhiqiang; Liu, Ningguo; Zou, Donghua; Huang, Ping; Chen, Yijiu
Abstract This case concerns a sudden death of a patient with Chiari I malformation. A 17‐year‐old female was seen unconscious then fell off a motorbike during the vehicle acceleration. The girl was confirmed dead on the way to hospital, being previously asymptomatic and with a clean medical record. Autopsy findings showed an extremely extra‐long cerebellar tonsillar herniation in the left side and unexplained multiple small cavities in cerebral hemispheres. Microscopic findings revealed loss and abnormal migration of the Purkinje cells, as well as capillary congestion in the herniated tonsil. The cause and mechanisms of this sudden death are considered as the cardiopulmonary dysfunction and arrest resulted from compression of the medulla and cervical cord, which was induced by both the positional insult and minor head trauma. In addition, this study stresses the importance of cervical cord examination in the case of unexpected sudden death following road accidents.